БІДНІСТЬ І НЕРІВНІСТЬ ЯК ЗАГРОЗА РОЗВИТКУ ЛЮДСЬКИХ МОЖЛИВОСТЕЙ (Zaporizhzhia Historical Review, 2021)
The negative influence of poverty and inequality on the human opportunities development and on the development of the country is examined in the article. The existence of the so-called ìvicious circlesî that connect non-realized human opportunities with poverty and inequality is being especially noted by the author.